Analisis Penerimaan dan Penggunaan Jamsostek Mobile Menggunakan UTAUT Model Modifikasi - Akbarida, Bramantyo Dhuha; Lukiastuti, Fitri; Solovida, Grace Tiana; Sutanto, Himawan Arif (Sekolah Tinggi Ilmu Ekonomi Bank BPD Jateng, 2024)
This study aims to analyze the factors that influence behavior intention for and use behavior of the Jamsostek Mobile application with a focus on the variables of performance expectancy, effort expectancy, social influence, facilitating conditions, habit, and perceived trust. The sampling technique used in this study was purposive sampling so that 160 respondents were obtained. The results showed that performance expectancy, effort expectancy, social influence, facilitating conditions, habit, and perceived trust have a positive and significant effect on behavioral intention. Behavioral intention has a positive and significant effect on use behavior. Behavioral intention is able to mediate the effect of performance expectancy, effort expectancy, social influence, facilitating conditions, habit and perceived trust on use behavior. User characteristics such as gender, age, education level, occupation, and length of membership play an important role in determining the active user base of the Mobile Social Security application, with specific demographics dominant among active users.